A New Record of Rochia maxima (Koch, 1844) Through a Species Clarification of Lola Snail, Bangka Belitung Islands, Indonesia - Aisyah, Siti; Pringgenies, Delianis; Supratman, Okto; Wahyudi, Dimas; Rizal, Fahmi; Ariyanto, Dafit; Arbi, Ucu Yanu (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Lola snails originating from the Bangka Belitung Islands (Nasik Strait, Rebo Waters, and Ketawai Island) were identified as a maxima not to be R. nilotica species based on morphological molecular identification. Maxima and R. nilotica have the same morphological form, but they are genetically different. The clarification of the Lola snail species in this study serves as a reference in determining the conservation status of the Lola snail. The clarification of the Lola snail species serves as a reference in determining the catch quota from the Bangka Belitung Islands. Abstract The use of Lola snails (Rochia maxima) in the Bangka Belitung has continued to increase. However, research focused on Lola snails originating from the Bangka Belitung has not been thoroughly conducted. In a previous study, the Lola snail sample found in the Bangka Belitung was Trochus niloticus (current name: Rochia nilotica). This study aimed to identify Lola snail species using the DNA barcoding as a way of clarifying Lola snail species that originated in the Bangka Belitung. Lola snail sampling was carried out at three locations, which were Nasik Strait, Ketawai, and Rebo Waters. This study was conducted through five stages, including Lola snail tissue sampling, DNA extraction, amplification by PCR, sequencing, and data analysis. The results showed that the molecular identification of the Cytochrome Oxidase Subunit 1 (COI) gene in Lola snail samples was identified as Rochia maxima species (Koch, 1844). The results of the phylogenetic tree analysis showed that Lola snails found in the Bangka Belitung were close to Tectus maximus (or Rochia maxima) species. R. maxima has a lighter shell than R. nilotica, a clear conical shape, and a circle on the body that does not widen at the edges. Unlike zoologists who said that R. maxima is the primitive form of R. nilotica, the present study found that they have the same morphology and are considered similar but genetically different. The clarification of Lola snail species can be used to determine the conservation status and catching quota of Lola snails from the Bangka Belitung.